SWK-07. Family mental health screening early after a diagnosis of pediatric brain tumor. (3rd June 2022) - Rodemann, Ashley; Hartmann, Mary; Limbrick, David; Abdelbaki, Mohamed; Cluster, Andrew
Abstract: INTRODUCTION: A new diagnosis of a brain tumor in a child has significant emotional consequences for every member of the family. Nevertheless, early phases of oncologic care rarely provide formal mental health screening. METHODS: We implemented a mental health screening protocol for families and patients with a newly diagnosed brain tumor admitted to our pediatric intensive care unit (PICU) at the time of diagnosis. Screening instruments were selected based on their previous validation and relevance to both a brain tumor diagnosis and PICU admission. Parents were contacted by a member of our team within 2 weeks of their child's diagnosis, and completed the screening independently within the next 2 weeks via an online interface. Parent proxy reports for the children were used when necessary. Scores were shared with the family and neuro-oncology team. When indicated, supportive counseling was offered. RESULTS: Eighteen patients have met criteria for mental health screening. Of these, 8 patient and parent dyads have completed the screening (mean patient age 8.6 years; 75% white; 50% female). Of the families that completed the evaluation, most parents (62.5%) reported that their child's diagnosis negatively impacted their health-related quality of life (HRQL), while 87.5% of children themselves reported a lower HRQL. Most children (66.7%) self-reported having symptoms outside of normal range for anger, anxiety and depression and 100% had scores outside of normal range for pain interference with their daily lives. Only half of eligible families accepted referrals for new mental health support. CONCLUSION: Both children with a new diagnosis of brain tumor and their parents are at risk for impaired mental health and quality of life early after diagnosis. A systematic approach to these concerns at the time of diagnosis may be helpful.